Heterogeneous Cross‐Linking and Sulphation of Chitosan. Issue 1 (December 2014) - Höhne, Susanne; Breier, Annette; Jäger, Maria; Hanke, Thomas; Worch, Hartmut; Simon, Frank; Lendlein, Andreas; Domb, Abraham J.
Summary Chitosan textile scaffolds are novel promising biomaterials for application in tissue engineering. The introduction of sulphate groups in the chitosan molecule leads to a biomaterial that combines two important features. At first it's an excellent material in order to build scaffolds for tissue engineering, and at second it is able to mimic the beneficial interaction of natural occurring sulphated polysaccharides with growth factors. Known sulphating methods, developed for the sulphation of chitosan in solutions (homogeneous phase reactions), were adapted to apply them on solid chitosan surfaces (heterogeneous phase reactions). Surface reactions preventing the chitosan's dissolution were fundamentally necessary to keep the predetermined geometric structure of the scaffolds during derivatization reactions. Model studies were carried out on chitosan particles as well as chitosan textiles. Points of interests were the control of the regioselectivity of the sulphation reactions and the adjustment of the degree of sulphation. It was shown that a partial cross‐linking of chitosan is a key tool to keep the geometric structure of the chitosan particles and fibres during the subsequent sulphation reaction. The modified samples were comprehensively characterized by means of X‐ray photoelectron spectroscopy and elemental analysis.